2021
DOI: 10.1136/bmjopen-2020-048423
|View full text |Cite
|
Sign up to set email alerts
|

Critical care service delivery across healthcare systems in low-income and low-middle-income countries: protocol for a systematic review

Abstract: IntroductionCritical care in low-income and low-middle income countries (LLMICs) is an underdeveloped component of the healthcare system. Given the increasing growth in demand for critical care services in LLMICs, understanding the current capacity to provide critical care is imperative to inform policy on service expansion. Thus, our aim is to describe the provision of critical care in LLMICs with respect to patients, providers, location of care and services and interventions delivered.Methods and analysisWe … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 16 publications
2
1
0
Order By: Relevance
“…A containment of LOS times and an improvement in the outcome of some categories of patients was observed as well [81][82][83][84][85][86][87][88]. These findings were in line with data from several other European and American research groups [89][90][91][92][93][94].…”
Section: Microlevel Strategiessupporting
confidence: 82%
“…A containment of LOS times and an improvement in the outcome of some categories of patients was observed as well [81][82][83][84][85][86][87][88]. These findings were in line with data from several other European and American research groups [89][90][91][92][93][94].…”
Section: Microlevel Strategiessupporting
confidence: 82%
“…An Italian research group showed that over the years of operation of an OBI team, a stabilization of the phenomena of “boarding” and “exit block” was observed, despite an increase in the number of ED admissions and the need for hospitalization of the patients themselves. A containment of the length of stay and improvement in the outcomes of some categories of patients was also observed [ 10 ]; these results are in line with data from other European and American research groups [ 10 , 60 , 61 ].…”
Section: Resultssupporting
confidence: 82%
“…The methods for this review have been published previously [14]. In summary, controlled vocabulary terms and text words related to critical care in LLMICs were developed.…”
Section: Methodsmentioning
confidence: 99%